Makna Pendidikan Islam dalam Ritual Masyarakat Jawa Mangan Longan Turu Longan - Robingun Suyud El Syam; Salis Irvan Fuadi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This article attempts to reveal the meaning of Islamic education in the Javanese ritual of Mangan Longan Turu Longan, by focusing on exploring what is done in the ritual so that it can map the form of the activity and its meaning. The article is a finding from the literature review research design, referring to the literature obtained by the researcher as a data source and as a reference for the theoretical basis and results found in the research. The results of the research show: that the Mangan Longan Turu Longan ritual contains the moral essence of a ritual that is carried out by reducing eating and sleeping by fasting and increasing the remembrance of Allah SWT. This will sharpen the mind so that the perpetrator becomes a strong person in navigating life's problems. This research is expected to contribute to the philosophy of Islamic education.